1996
DOI: 10.1128/mcb.16.2.685
|View full text |Cite
|
Sign up to set email alerts
|

E2F-1 Blocks Terminal Differentiation and Causes Proliferation in Transgenic Megakaryocytes

Abstract: The transcription factor E2F-1 plays a central role in the cell cycle through its ability to activate genes involved in cell division. E2F-1 activity is regulated by a number of proteins, including the retinoblastoma susceptibility gene product, cyclin-dependent kinases, and their inhibitors, proteins that have been implicated in the control of certain developmental processes. To investigate a potential role of E2F-1 in differentiation, we assayed the ability of megakaryocytes to form platelets in an in vivo t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 53 publications
3
49
0
Order By: Relevance
“…Overexpression of E2F-1 in di erentiated cells is able to override the downregulation of proliferation markers (cdc2 and K14) and is also able to suppress the subsequent induction of the di erentiation speci®c genes Transglutaminase Type I and keratin 10. The ability of E2F-1 to inhibit di erentiation has been demonstrated in a number of other tissues including blood cells (Guy et al, 1996;Strom et al, 1998), muscle (Wang et al, 1995(Wang et al, , 1996Tiainen et al, 1996), and neural tissue (Suda et al, 1994;Neuman et al, 1995), suggesting that E2F-1 may play a role in controlling the normal di erentiation process. However, it was not evident in those studies whether E2F-1 operated simply by maintaining the proliferative state of cells or whether it could also actively participate in the suppression of di erentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of E2F-1 in di erentiated cells is able to override the downregulation of proliferation markers (cdc2 and K14) and is also able to suppress the subsequent induction of the di erentiation speci®c genes Transglutaminase Type I and keratin 10. The ability of E2F-1 to inhibit di erentiation has been demonstrated in a number of other tissues including blood cells (Guy et al, 1996;Strom et al, 1998), muscle (Wang et al, 1995(Wang et al, , 1996Tiainen et al, 1996), and neural tissue (Suda et al, 1994;Neuman et al, 1995), suggesting that E2F-1 may play a role in controlling the normal di erentiation process. However, it was not evident in those studies whether E2F-1 operated simply by maintaining the proliferative state of cells or whether it could also actively participate in the suppression of di erentiation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, E2F-1 has been reported to (i) be oncogenic (Johnson et al, 1994;Pierce et al, 1998); (ii) act as a tumour suppressor (Yamasaki et al, 1996); (iii) promote apoptosis (Shan and Lee, 1994;Qin et al, 1994); (iv) transform cells (Yang and Sladek, 1995;Sladek, 1996); or (v) block di erentiation (Wang et al, 1995;Guy et al, 1996). The most likely explanation for these opposing e ects may be attributed to cell type-restricted functions for E2F-1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to promoting proliferation, E2F1 has also been shown to block di erentiation in several model systems Guy et al, 1996). Despite the increased thickness and cellularity of the epidermis, the terminal di erentiation program is maintained in K5 E2F1 transgenic mice as evidenced by the presence of apparently normal spinous, granular, and corneal layers (Figure 3).…”
Section: Hyperplasia and Apoptosis In K5 E2f1 Transgenic Micementioning
confidence: 99%
“…E2F1 expression can also bypass a G1 phase growth arrest induced by Rb, p16/INK4A, TGF-b, and gamma irradiation (Zhu et al, 1993;Lukas et al, 1996;Schwarz et al, 1995;DeGregori et al, 1995a). Ectopic E2F1 expression has also been found to inhibit terminal di erentiation in both in vitro and in vivo model systems Guy et al, 1996). In addition, several groups have demonstrated that under some circumstances E2F1 can induce a variety of cell types to undergo programmed cell death or apoptosis in a p53-dependent manner (Wu and Levine, 1994;Qin et al, 1994;Hiebert et al, 1995;Kowalik et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic expression of E2F1 leads to apoptosis in tissue culture cells [3][4][5] and transgenic mice. [6][7][8] Moreover, a physiological role for E2F1-mediated apoptosis is suggested by the observation that mice deficient in E2F1 have an excess of mature T cells due to a defect in thymocyte apoptosis. 9 E2F1-induced apoptosis occurs via both p53-dependent and -independent pathways.…”
Section: Introductionmentioning
confidence: 99%